Transmembrane signaling by a chimera of the Escherichia coli aspartate receptor and the human insulin receptor. - Moe, G R (1989)
Since many receptors apparently contain only one or two membrane-spanning segments, their transmembrane topology should be similar. This feature suggests that these receptors share common mechanisms of transmembrane signaling. To test the degree of conservation of signaling properties, a chimeric receptor containing the ligand-binding extracellular domain of the Escherichia coli aspartate chemoreceptor and the cytosolic portion of the human insulin receptor was constructed. This chimeric receptor is active as a tyrosine kinase, and aspartate stimulates its activity. Some interesting differences are noted in the target proteins phosphorylated by the chimera compared to the wild-type insulin receptor. These results indicate that features of the signaling mechanisms used by these diverse receptors are conserved, but that interesting changes in the protein properties are caused by differences in the neighboring domains.